Analisis Model Role Playing untuk Meningkatkan Motivasi Belajar PAI dalam Perspektif Filsafat Ilmu - Dirja, Muldani Surya; Fatimah, Siti (Prodi Pendidikan Keagamaan Islam, 2025)
This study aims to analyze the application of role-playing learning models in increasing extrinsic motivation to learn Islamic Religious Education (PAI) of fifth-grade students at SDIT Buah Hati Air Tawar Barat Padang, then linked to the perspective of the philosophy of science: knowledge. This research is motivated by the problem of students' lack of enthusiasm and motivation to learn, so a learning model that can improve this is needed. This study uses a qualitative method with a case study approach. Overall, the results of the analysis show: there are several steps to implement it, namely: the teacher provides stimulus and explanations to students; the teacher provides learning motivation to students; the teacher provides scenario scripts in the form of dialogue conversations to all students; the teacher allows students to choose their group mates, and so on. When viewed from the perspective of the philosophy of science: knowledge, this research is categorized as a science because of the truth of the theory that role-playing models can indeed increase students' learning motivation, through investigations that researchers conducted in the field according to the rules of the scientific method.